P017 Variations in clinical practice in paediatric rheumatology units as a result of the COVID-19 pandemic: Initial findings of a UK wide Multi-Centre Survey. (23rd April 2022) - McLaughlin, Diarmuid; Deepak, Samundeeswari
Abstract: Background/Aims: To understand the impact of COVID-19 on UK paediatric rheumatology services, to determine the learning points that could change future practice and provide information for trainees to plan further quality improvement projects. Methods: Survey details with a Microsoft forms link were emailed to consultants in each UK paediatric rheumatology centre. Consultants were asked to forward the survey onto any regional units linked. The survey was also sent to the paediatric rheumatology trainee's network. The questionnaires covered blood monitoring, joint injections, oral corticosteroid use, modes of consultations, positive and negative impacts and what changes should be carried forward. Results: 20 staff responded to the survey; 17 consultants and three trainees (registrar level). 85% (17) reported changes had occurred to the frequency of blood monitoring to rheumatology patients on Disease Modifying Anti-Rheumatic Drugs (DMARDs) and/or biologics during the pandemic. 60% (12) reported this was due to patient/family reluctance to attend or due to unavailability of appointments. 75% (15) recorded no complications following changes of blood frequency on disease activity or flare. Of those that did have a flare, a number of factors were described including: parents not contacting their service, patient/family discontinuation of treatment, lack of clinic attendance, running out of treatment and safety concerns re prescribing from primary care or local department. One patient on methotrexate experienced significantly deranged liver function tests.75% (15) reported changes with provision of joint injections due to theatre unavailability. As a consequence, 60% (12) reported an increase in the use of oral corticosteroids with 20% (4) performing more ward-based injections with local anaesthetic or Entonox on younger children. 100% (20) changed their mode of consultation. Between 5 and 40% of all appointments are now virtual (telephone or video) and 60-95% are face-face. 60% (12) report that frequency of review appointments has now returned to normal. Major disruption has occurred in seeing new patients due to a backlog of patients created by the pandemic. Some patients have been referred to units with possible arthritis that haven't been examined or seen face-face in primary care prior to referral. Conclusion: COVID-19 caused significant changes to UK paediatric rheumatology services. The results highlighted the use of virtual consultations where appropriate, consideration of joint injections without general anaesthetic as much as possible, enabling virtual teaching/conferences and also raising the need to review blood monitoring frequency for patients on DMARDs/biologics. Longer waiting lists, increased anxiety amongst children and young people, increase in disease activity and the impact on learning opportunities for trainees were concerning negative aspects of the pandemic. It is likely the impact of these negative consequences will continue to be experienced for some time. Future planning and consideration is required to minimise the negative impact of these aspects on our patients and colleagues. Disclosure: D. McLaughlin: None. S. Deepak: None.